Variasi Temperatur Dan Rasio Putaran Pada Hammer Mill Dan Screw Conveyor Flash Drayer Terhadap Hasil Pengeringan - Sagita, Dimastya Adi; , Ir. Sartono Putro, MT (2016)
The process of making flour made of settled extract, in order to make it durable needs drying process. The drying process is a process removing water which contained in an ingridient. The flour drying process needs a tool calls flashdryer. In this research, the flashdryer machine uses 1:2,67 , 1:3,33 ,1:4 comparison of hammer mill and conveyor with 90°C,100°C,110°C temperature. Inside the flash dryer the wet flourdough is put into the screw conveyor and hammer mill for the next step to be soften and to be warmed by hot air in continue until the flour well dried. The research result has shown that rotation of hammer mill and screw conveyor, and the influence of temperature which given by water heater which influence the drying result so much. A higher comparison of hammer mill and screw conveyor and a higher air temperature there will be a lower water content produced in the dryer process. The most optimal result get from the comparison is rotation 1:4 with temperature 110°C.